Some Issues on Reforming the Legislation on Administrative Offences - S. I. Koryts; I. B. Bokova (Сибирское юридическое обозрение, 2019)
Some problems of modern administrative-tort law are considered. Attention is focused on a number of key problems of the current legislation on administrative offenses and on some specific proposals for its amendment. The possible consequences of the adoption of these proposals are analyzed. The need for a systematic approach to reforming existing legislation on administrative offenses is noted. It is proposed to develop a truly workable mechanism for determining the size of the fine imposed, which would make it possible to objectively take into account the social harmfulness of the misconduct, the real property situation of the offender, and other relevant circumstances that will serve the preventive purpose of sentencing to the maximum effect. It is concluded that it is necessary to systematize and thoroughly analyze the currently existing law enforcement problems and develop ways to solve them, taking into account the concept of the new Code of the Russian Federation on Administrative Offenses.